Combating a deadly menace : early experiences with a community-based arsenic mitigation project in Bangladesh - Chowdhury, A. M. Raza.; BRAC. Research and Evaluation Division (Dhaka : BRAC, Research and Evaluation Division, 2000)
Report of project "Action Research into Community-Based Arsenic Mitigation" implemented in Narayanganj and Jessore districts.
Includes bibliographical references (pages 88-89).
Keywords: Groundwater pollution -- Bangladesh; Arsenic -- Toxicology -- Bangladesh; Arsenic -- Environmental aspects -- Bangladesh; Water -- Purification -- Arsenic removal -- Bangladesh